1992
DOI: 10.1016/0891-5849(92)90079-v
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen radicals in ulcerative colitis

Abstract: This article reviews the pathophysiologic concept that superoxide and hydrogen peroxide, generated by activated leukocytes, together with low-molecular-weight chelate iron derived from fecal sources and from denatured hemoglobin, amplify the inflammatory response and subsequent mucosal damage in patients with active episodes of ulcerative colitis. The putative pathogenic mechanisms reviewed are as follows: ( l ) Dietary iron is concentrated in fecal material owing to normally limited iron absorption. (2) Mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
175
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(177 citation statements)
references
References 59 publications
1
175
0
1
Order By: Relevance
“…Apoptotic cell death is accompanied with activation of various cell death pathways including caspases, ceramide, altered gene expression, mitochondrial dysfunction and consumption of ATP [4,5] . Although these signals and metabolic events may be important in the regulation of cell death, cell death pathways are also associated with the secondary production of oxidants that appears to contribute to the magnitude of cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptotic cell death is accompanied with activation of various cell death pathways including caspases, ceramide, altered gene expression, mitochondrial dysfunction and consumption of ATP [4,5] . Although these signals and metabolic events may be important in the regulation of cell death, cell death pathways are also associated with the secondary production of oxidants that appears to contribute to the magnitude of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal lesion in inflammatory bowel disease (IBD) is characterized by dense inflammatory cell infiltrate mainly comprised of neutrophils, macrophages and lymphocytes. Although many inflammatory mediators secreted by these cells, including cytokines IL-1, IL-6, IL-8, IL-10, TNF- and leukotrienes together with luminal bacterial products such as bacterial lipopolysaccharide (LPS) and chemotactic peptide fMLP, have been implicated in the mucosal injury observed in IBD [3] , and the molecules that mediate tissue damage remain poorly understood [4][5][6][7] . Recent indirect evidence has, however, implicated reactive oxygen and nitrogen species (RONS) such as nitric oxide (NO), superoxide (O 2 -), peroxynitrite (ONOO -), hydrogen peroxide (H 2 O 2 ), and hypochlorite (OCl -) in the pathogenesis of mucosal lesion [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…10 The cell's water-soluble antioxidants include vitamin C, glutathione peroxidase, SOD, and catalase. [30][31][32][33] It has been speculated that free radical generation by the mitochondrial respiratory chain contributes to the pathophysiology of CRPS I. [34][35][36] Eisenberg et al demonstrated significant increases in malondialdehyde, lactic dehydrogenase, and antioxidants (peroxidase, superoxide dismutase, uric acid) in the serum and especially the saliva of CRPS I patients compared to healthy controls.…”
Section: Interventional Therapiesmentioning
confidence: 99%
“…The most important free radicals are oxygen derivatives-particularly superoxide anion (O 2 -•), hydroxyl radical (OH-), and hydrogen peroxide (H 2 O 2 )-and reactive nitrogen species such as nitric oxide and peroxynitrite. 31,32 Therapeutic Approach…”
Section: Definition and Role Of Oxidative Stress In Crps Pathogenesismentioning
confidence: 99%
“…Our previous study revealed an anti-colitis effect of Kurozu (3), and oxidative and nitration stress are known to be involved in the pathogenesis and severity of UC (4). Therefore, we chromatographically fractionated Kurozu and investigated the protective effects of four molecular-weight fractions against DSS-induced colitis in mice, focusing on anti-oxidative and anti-nitration stress activity.…”
Section: Introductionmentioning
confidence: 99%